1997
DOI: 10.1172/jci119464
|View full text |Cite
|
Sign up to set email alerts
|

Myonuclear apoptosis in dystrophic mdx muscle occurs by perforin-mediated cytotoxicity.

Abstract: Myonuclear apoptosis is an early event in the pathology of dystrophin-deficient muscular dystrophy in the mdx mouse. However, events that initiate apoptosis in muscular dystrophy are unknown, and whether elimination of apoptosis can ameliorate subsequent muscle wasting remains a major question. We have tested the hypothesis that cytotoxic T-lymphocytes initiate myonuclear apoptosis in dystrophic muscle, and examined whether perforin-mediated cytotoxicity plays a role in the pathophysiology of muscular dystroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(137 citation statements)
references
References 50 publications
7
124
2
Order By: Relevance
“…Tissue preparation and immunohistochemistry were performed as described (13). Antibodies used for staining were rat anti-NCAM (Chemicon, mAB 310), rat anti-Mac 1 (PharMingen), anti-AchR␣ (Transduction Laboratories, Lexington, KY), and mouse anti-fast MHC (NovoCastra, Newcastle, U.K.).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue preparation and immunohistochemistry were performed as described (13). Antibodies used for staining were rat anti-NCAM (Chemicon, mAB 310), rat anti-Mac 1 (PharMingen), anti-AchR␣ (Transduction Laboratories, Lexington, KY), and mouse anti-fast MHC (NovoCastra, Newcastle, U.K.).…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 1, most of the deregulated pathways involved inflammatory/immune responses, including immune disease, immune system, and infectious disease. These immune/inflammatory pathways mainly indicated the infiltration of immune cells, such as T cells (McDouall et al, 1990;Spencer et al, 1997), macrophages (McDouall et al, 1990;Spencer et al, 1997), eosinophils (Cai et al, 2000), and mast cells (Granchelli et al, 1995;Nahirney et al, 1997), into muscles and elevated levels of various inflammatory cytokines. A previous study showed that in vivo depletions of CD4 or CD8 T cells or macrophages (Wehling et al, 2001) significantly reduced the pathology in mdx mice, and that the efficacy of the only drugs currently available for the treatment of DMD (glucocorticoids) in delaying DMD progression is mainly based on the suppression of inflammation (Serra et al, 2012), implicating the important roles of immune/ inflammation responses in aggravating the disease.…”
Section: B Discussionmentioning
confidence: 99%
“…In addition, most of the pathways in which aberrantly regulated enriched genes were involved resulted in an inflammatory/immune response. This may result from the infiltration of immune cells into the muscles (Mcdouall et al, 1990;Spencer et al, 1997;Cai et al, 2000) and also in elevated levels of various inflammatory cytokines. For muscle regeneration, two genes which encode embryonic and perinatal myosin heavy chains (MYH3 and MYH8) were overexpressed, consistent with Haslett et al (2002).…”
Section: Discussionmentioning
confidence: 99%